The strength, position, and width changes of the intertropical convergence zone since the Last Glacial Maximum - Yuan, Shufang (2024)
The intertropical convergence zone (ITCZ) plays a key role in regulating tropical hydroclimate and global water cycle through changes in its convection strength, latitudinal position, and width. The long-term variability of the ITCZ, along with the corresponding driving mechanisms, however, remains obscure, mainly because it is difficult to separate different ITCZ variables in paleoclimate proxy records. Here, we report a speleothem oxygen isotope (δ18O) record from southwestern Sulawesi, Indonesia, and compile it with other speleothem records from the Maritime Continent. Using the spatial gradient of speleothem δ18O along a transect across the ITCZ, we constrain ITCZ variabilities over the Maritime Continent during the past 30,000 y. We find that ITCZ convection strength overall intensified from the last glacial period to the Holocene, following changes in climate boundary conditions. The mean position of the regional ITCZ has moved latitudinally no more than 3° in the past 30,000 y, consistent with the deduction from the atmospheric energy framework. However, different from modern observations and model simulations for future warming, the ITCZ appeared narrower during both the late Holocene and most part of the last glacial period, and its expansion occurred during Heinrich stadials and the early-to-mid Holocene. We also find that during the last glacial and deglacial period, prominent millennial-scale ITCZ changes were closely tied to the variability of the Atlantic meridional overturning circulation (AMOC), whereas during the Holocene, they were predominantly modulated by the long-term variability of the Walker circulation.